Realitas Ilmu Sosial Pada Pendidikan Ilmu Pengetahuan Sosial - Ivan Sanjaya; Rudy Gunawan (CHRONOLOGIA, 2021)
This study aims to see the extent to which social attitudes and roles in the education unit environment are provided and provided through Social Science Education in the Bethel Dadap Basic Education Unit based on the curriculum journey and in the current digital era. This study uses a qualitative method using a document study instrument or can be called a literature study. The results of this study indicate that technological sophistication also has a negative impact on students, one of which is causing these students to have apathy. Although it is undeniable on the one hand, technological advances also provide various conveniences in human life. Therefore, in this case, it is very important to have cooperation between teachers and students' guardians in order to maximize the social studies learning process in schools so that it can be applied in social life. In addition, from this study it was found that the implementation of the social studies curriculum at Bethel Dadap Elementary School went well because it paid attention to every aspect of the social studies learning indicators.